A tactile discrimination task to study neuronal dynamics in freely-moving mice - Heimburg, Filippo; Saluti, Nadin Mari; Timm, Josephine; Adlakha, Avi; Bortolozzo-Gleich, Maria Helena; Martín-Cortecero, Jesús; Castelanelli, Melina; Klumpp, Matthias; Embray, Lee; Both, Martin; Kuner, Thomas; Groh, Alexander (Nature communications, 2025)
Sensory discrimination tasks are valuable tools to study neuronal mechanisms of perception and learning, yet most rodent paradigms rely on head fixation. Here, we present a whisker-dependent go/no-go discrimination task for freely moving mice, compatible with high-resolution electrophysiology and calcium imaging. Adult male mice rapidly learned to discriminate aperture widths while foraging on a linear platform, enabling investigations of tactile thresholds, rule reversals, and behavioral flexibility. Neural recordings revealed distributed tactile coding across the thalamocortical system, with units tuned to both sensory and motor features, including whisking, head angle, and spatial position. Aperture selectivity emerged in the barrel cortex during learning, and cortical lesions impaired performance, highlighting cortical involvement in learning and task execution. The setup is modular, automated, and supports simultaneous recordings and imaging aligned to naturalistic behavior. This platform provides a powerful tool to dissect sensory processing and learning in ethologically relevant conditions. Task paradigms allowing studies on the core ethological function of the whiskers are lacking. Authors here present a task for freely moving mice that enables the study of how the brain processes touch and learns. The setup combines behavior, electrophysiology, and imaging, offering insights into naturalistic sensory and decision-making processes.